Conectividade e variabilidade genética do tubarão galha-branca oceânico, Carcharhinus longimanus, usando DNA mitocondrial - Camargo, Sâmia Mouallem de [UNESP] (2015)
Until few decades ago, shark catching was considered to be only incidental and with no significant effects on their populations. However, the great increase in the fins market value combined with declining levels of traditional fish population for human consumption, sharks have become targets of the fisheries worldwide. Among these, the whitetip shark Carcharhinus longimanus shows strong signs of population depletion, and is currently listed as globally Vulnerable according to the Red List of Threatened Species of the International Union for Conservation of Nature. Regarding conservation plans, acquiring knowledge about the population genetic structure of the species is a fundamental step towards establishing effective conservation policies. Considering the limited information about population dynamics of the oceanic whitetip shark, were used partial sequences of the mitochondrial DNA (mtDNA) control region to determine its population genetic structure across the Atlantic Ocean and the Indian Ocean. Were sampled 215 specimens of C. longimanus and obtained 724 base pairs (bp), identifying nine polymorphic sites, which resulted in 12 distinct haplotypes. The total nucleotide diversity was π = 0.0013 and haplotype diversity h = 0.5953. These results show a genetic variability slightly below the observed average among other species of pelagic sharks. The Analysis of Molecular Variance (AMOVA) evidenced moderate levels of population structure (FST = 0.1039, P<0.001) with restriction of gene flow between the Western and Eastern Atlantic Ocean with a strong relationship of this latter with the Indian Ocean. Thus, for the expansion of conservation plans of the species, also for the maintenance of their genetic stocks, should be considered at least two populations in the Atlantic Ocean and more attention to areas where the greatest genetic diversity indexes were found. As the acquisition of information about the environmental causes that are...